Evidence of negative relationship between female fertility and feed efficiency in Nellore cattle - Ferreira Junior, Rubens J.; Bonilha, Sarah F. M.; Monteiro, Fabio M.; Cyrillo, Joslaine N. S. G.; Branco, Renata H.; Silva, Josineudson A. I. I. V. [UNESP]; Mercadante, Maria Eugenia Z. (Oxford Univ Press Inc, 2018)
The objective of this study was to evaluate phenotypic and genetic relationships between fertility traits and feed efficiency in male and female Nellore cattle. Data from 320 females born between 2004 and 2011 were used for phenotypic evaluation. These animals were evaluated for postweaning residual feed intake (RFI) and classified as negative (RFI < 0, mean = -0.294 +/- 0.017 kg DM/d) or positive RFI (RFI > 0, mean = 0.305 +/- 0.0189 kg DM/d). Of these, 118 prepuberal heifers were submitted to ultrasonography of the uterus and ovaries for monitoring the presence (or absence) of a corpus luteum and for the measurement of endometrial thickness. The following fertility traits were evaluated in all females: age at first calving, days to calving, first calving interval, calving success, stayability, and longevity. The variance components were estimated by the average information restricted maximum likelihood method under an animal model in 5-trait analysis of backfat and rump fat thickness, scrotal circumference, days to calving, and RFI. The total number of animals with records was 6,718, including 927 males with records of scrotal circumference and RFI and 264 females with records of days to calving and RFI. Negative RFI females consumed 12.5% less DM daily than positive RFI females and had a lower rump fat thickness when evaluated postweaning. Among the fertility traits studied, only first calving interval differed (P = 0.0858) between RFI classes, with the interval of negative RFI females being 45 d shorter than that of positive RFI animals. The heritability estimates were 0.29, 0.34, 0.50, 0.12, and 0.16 for backfat and rump fat thickness, scrotal circumference, days to calving, and RFI, respectively. The genetic correlations between RFI and the other traits studied were unfavorable for selection and were of moderate magnitude with backfat thickness, rump fat thickness, and days to calving (0.53, 0.37, and -0.49, respectively) and close to zero with scrotal circumference (0.07). Scrotal circumference (0.17 and 0.15) and days to calving (-0.10 and -0.22) were weakly and favorably correlated with backfat and rump fat thickness. There is evidence of moderate genetic antagonism between female fertility and feed efficiency, but with no evidence of a genetic correlation between male fertility and feed efficiency. There is also evidence of low genetic synergism between fat thickness and fertility.
Keywords: beef cattle; days to calving; feed efficiency; genetic parameters; scrotal circumference